Efecto de la edad del pasto kikuyo (Pennisetum clandestinum) y la relación forraje : concentrado sobre la metanogénesis (2015)
ABSTRACT: To evaluate the effect of Kikuyu grass (Pennisetum clandestinum) harvested at two different ages and three forage: concentrate supplement ratios (F/C) on methane (CH4) production, dry matter digestibility (DMD), and fermentation profile using the in vitro gas production technique. Materials and methods. six treatments, resulting from the combination of pasture age (30 or 60 days) and F/C (100/0, 75/25, or 50/50) were evaluated using a 2x3 factorial design. The response variables were measured 6, 12, 24 and 48 hours after incubation. A repeated-measure over time design was used to analyze the data, and differences between means were determined with the LSMEANS procedure of SAS. Results. the youngest grass (30 days) was more digestible, produced less CH4 per gram of digestible dry matter (dDM) and more total volatile fatty acids (VFA) compared to the oldest grass (60 days; p <0.05). Reductions of the F/C ratio increased DMD and CH4 production per gram of dDM (p<0.05) but had no significant effect on VFA concentration (p>0.05). Conclusions. under in vitro conditions and pH close to neutrality, the older grass reduces DMD and increases CH4 production per gram of dDM, while a F/C reduction increases DMD and CH4 production per gram of dDM, which differs with reports conducted in vivo. Key words: Carbohydrates, in vitro digestibility, grass maturity, methane production (Sources: CAB, USDA).